The Model of Elderly Health Care Based on the Four Foundations of Mindfulness at Ban Kham Pia Subdistrict Health Promoting Hospital - Wiriyakhunnasan, Phrakhru; Sudhikhambhirayan, Phrakhru; Saypakhom, Intong (Journal of Graduate MCU KhonKaen Campus, 2024)
This research aims to 1) study elderly health care based on the Four Foundations of Mindfulness at Ban Kham Pia Subdistrict Health Promoting Hospital, Ban Haet Subdistrict, Ban Haet District, Khon Kaen Province; 2) study the model of elderly health care based on the Four Foundations of Mindfulness at Ban Kham Pia Subdistrict Health Promoting Hospital, Ban Haet Subdistrict, Ban Haet District, Khon Kaen Province; 3) propose a model of elderly health care based on the Four Foundations of Mindfulness at Ban Kham Pia Subdistrict Health Promoting Hospital, Ban Haet Subdistrict, Ban Haet District, Khon Kaen Province. This research uses qualitative research methods, collecting data through in-depth group discussions with 30 key informants, and analyzing and presenting the data descriptively. Research Findings: Elderly health care based on the Four Foundations of Mindfulness at Ban Kham Pia Subdistrict Health Promoting Hospital, Ban Haet Subdistrict, Ban Haet District, Khon Kaen Province, consists of four aspects: 1) Physical care, personality, and potential, by practicing mindfulness to avoid harmful behaviors; 2) Social awareness of human values by living together happily; 3) Mental relaxation and stability through the practice of mindfulness meditation; and 4) Analytical thinking and reasoning, utilizing in-depth knowledge to improve overall health, leading to a better quality of life. The model of elderly health care based on the Four Foundations of Mindfulness at Ban Kham Pia Subdistrict Health Promoting Hospital, Ban Haet Subdistrict, Ban Haet District, Khon Kaen Province, comprises four aspects: 1) Promoting lifelong learning; 2) Health care with a human-centered approach; 3) Flexible working practices; and 4) Community participation in elderly health care. The proposed model of elderly health care based on the Four Foundations of Mindfulness at Ban Kham Pia Subdistrict Health Promoting Hospital, Ban Haet Subdistrict, Ban Haet District, Khon Kaen Province, includes three forms: 1) Establishing a community hospice; 2) Creating a Buddhist health charter; and 3) Providing home health care services for the elderly.